Combustion generated nanomaterials: online characterization via an ICP-MS based technique. Part I: calibration strategy with a TGA. Issue 9 (14th August 2018) - Foppiano, D.; Tarik, M.; Gubler Müller, E.; Ludwig, C.
Abstract : Quantification strategy for combustion generated nanomaterials. Abstract : The coupling between a scanning mobility particle sizer (SMPS) and an inductively coupled mass spectrometry (ICP-MS) was in the past shown to obtain simultaneous size-resolved and elemental information on nanoparticles, using a rotating disc diluter (RDD) as conditioning and dilution system. A calibration strategy for the hyphenated RDD-SMPS-ICP-MS setup is presented here. Evaporation experiments of ZnCl2 powder were performed at four different temperatures, using a TGA as an aerosol source to correlate linearly the weight in loss of the TGA with the averaged ICP-MS intensities measured in transient mode. The calibration curve of Zn showed a good correlation factor ( R 2 = 0.9985) and a sensitivity of 20.95 × 10 3 counts ng −1 . The LoD (limit of detection) of the method was estimated to be ∼32 ng cm −3, once the total dilution of the whole setup is considered. A second set of experiments was performed, where ZnO and CaCl2 ·2H2 O powders were used as reactants to generate ZnCl2 particles. The output data of the two instruments were treated and appropriately converted, to allow a direct and quantitative comparison between the performances of SMPS and ICP-MS. The ICP-MS signal of Zn was quantified by using the external calibration performed with the coupling of a TGA with an ICP-MS, while the SMPS volume data used two general assumptions, namely spherical morphology and bulk density of ZnCl2 . Additional TEM analysis performed on the size-selected ZnCl2 particles allowed to check their morphology. The proposed calibration strategy of the ICP-MS signals enables to evaluate the SMPS quantification procedure.